ROLE STRESS AND TEACHER’S EFFECTIVENESS: A COMPARATIVE STUDY BETWEEN PUBLIC AND PRIVATE UNIVERSITY MAINSTREAM TEACHERS OF HARYANA (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Higher education is a cornerstone of national development, fostering a knowledge-based society through advanced learning and intellectual growth. This study examines the impact of role stress on teacher effectiveness among core faculty members in public and private universities of Haryana. Utilizing purposive sampling, data were collected from 187 public and 200 private university educators. The findings identified key stressors including inter-role distance, role stagnation, role overload, and role ambiguity. While private university faculty rated themselves as more effective, student evaluations indicated higher effectiveness among public university teachers. Role overload emerged as a common stressor across both sectors. The study establishes a significant negative correlation between role stress and teacher effectiveness, highlighting the critical need for institutional strategies to mitigate stress and enhance academic performance.